2009
DOI: 10.1007/s00268-009-0283-0
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic Determination of Breast Volume by Elliptical Cone Estimation

Abstract: Breast volume can be accurately determined from measurements made on mammograms. The proposed EC formula calculating breast volume on both the craniocaudal and the medial-lateral-oblique mammograms may be more accurate, as the horizontal and vertical dimensions of the breast are not always the same. In addition, height measurement on the medial-lateral-oblique film can eliminate the compression error as the craniocaudal film may miss the base of the breast and underestimate the breast volume. Taking both mammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Reports underline the importance of breast volume measurement both in determin-ing the best ORBS technique and obtaining more objective assessments of post-surgery cosmetic outcomes (22). Mammographic methods, while expensive, are highly popular due to their accuracy and repeatability (23). However, the most widely used method seen in our study was GRD.…”
Section: Discussionmentioning
confidence: 81%
“…Reports underline the importance of breast volume measurement both in determin-ing the best ORBS technique and obtaining more objective assessments of post-surgery cosmetic outcomes (22). Mammographic methods, while expensive, are highly popular due to their accuracy and repeatability (23). However, the most widely used method seen in our study was GRD.…”
Section: Discussionmentioning
confidence: 81%
“…Fung et al concluded that most accurate and reproducible formula for calculating breast volume was the one that assumed the elliptical cone projection rather than circular cone on mammogram [11] . Bullstrode found calculating the breast volume from mammography that has previously been compared to mastectomy samples shown to be reasonably accurate and therefore method of choice [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The following measurement methods were identified from included studies: anthropometric models [12,13], immersion in water (referred to as 'Archimedes' [12]), breast casts [12,32], the GrossmaneRoudner cone [12], computed tomography [38], magnetic resonance imaging [32,34,39], mammography [11,12,36,40,41] and 3D surface scanning [33,35,42e44].…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…Of the measurement methods used in this review, 3D scanning and mammography were the most favoured with five studies in both cases. It is worth noting that three 3D scanning studies assess differential, as opposed to absolute, volumes and one of the mammography studies [41] provided r values only, making indepth analysis difficult.…”
Section: Assessing Errormentioning
confidence: 99%
See 1 more Smart Citation